PENGEMBANGAN VIDEO SUMBER BELAJAR BERBASIS KEARIFAN LOKAL DI MIN 29 ACEH BESAR - Asfiana, Asfiana; Lessy, Zulkipli (PIONIR: JURNAL PENDIDIKAN, 2023)
This research was motivated by the fact that the media used in the learning process did not yet exist and only used learning resources from printed books. The results of the researcher's analysis of the printed books used showed that the books only contained descriptions of general material, and the teachers did not connect the material with local wisdom in the area where the students live. The objectives of this research are: (1) to describe the design for developing video learning resources based on the local wisdom; (2) to explain the feasibility of learning resource videos based on local wisdom, and (3) to explain the practicality of developing learning resource videos based on the local wisdom. The research method used is Research and Development (R&D), using the Alessi and Trollip models. The research results show that the learning resource videos based on local wisdom at MIN 29 Aceh Besar have met the very appropriate category based on the validation results of the material, so a score of 87.5% was obtained and the media validation results obtained a score of 90.8% with the criteria "very feasible". Meanwhile, the practical results of three class teachers obtained scores, namely: the class IV-A teacher scored 100%, the class IV-B teacher scored 100% and the class IV-C teacher scored 100% with the criteria "very worthy". Based on the research results, the video learning resources based on the local wisdom at MIN 29 Aceh Besar are very worthy of further development.